Bank Loans and the Transmission Mechanism of Monetary Policy - Kerstin Hallsten (Sveriges Riksbank, 1998)
How monetary policy affects the economy is a central topic of debate in macroeconomics. The bank lending channel is one approach that emphasises the role of banks. Banks are important because of asymmetric information in the financial market. Banks are assumed to be better at handling information problems than other lenders. In this paper it is analysed how monetary policy works when there is a bank lending channel and then it is tested for the importance of this channel using Swedish data.
Keywords: E50; 330; Bank loans; Transmission mechanism; Monetary policy